2016
DOI: 10.1016/j.hrthm.2015.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Infarct transmurality as a criterion for first-line endo-epicardial substrate–guided ventricular tachycardia ablation in ischemic cardiomyopathy

Abstract: The endocardial approach in patients with transmural MI undergoing VT substrate ablation is associated with an increased risk of recurrence. IT may be a useful criterion for the selection of a first-line combined endo-epicardial approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(42 citation statements)
references
References 30 publications
0
40
0
2
Order By: Relevance
“…We found epicardial LP in the majority of patients with IRA‐CTO that underwent epicardial mapping. In another study, endoepicardial mapping and ablation was found to be superior to an endocardial‐only approach in patients with transmural MI . Unfortunately, detailed information about the transmurality of the MI was not available for the majority of patients in our study.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…We found epicardial LP in the majority of patients with IRA‐CTO that underwent epicardial mapping. In another study, endoepicardial mapping and ablation was found to be superior to an endocardial‐only approach in patients with transmural MI . Unfortunately, detailed information about the transmurality of the MI was not available for the majority of patients in our study.…”
Section: Discussionmentioning
confidence: 67%
“…In another study, endoepicardial mapping and ablation was found to be superior to an endocardial-only approach in patients with transmural MI. 19 Unfortunately, detailed information about the transmurality of the MI was not available for the majority of patients in our study. However, it is highly proba- On the other hand, LP cannot always be abolished, possibly due also to limitations of radiofrequency as an energy source; contact force information and other newer ablation techniques might improve these results.…”
Section: Discussionmentioning
confidence: 94%
“…[23] Probably the greatest clinical impact was related to electrophysiology procedural decisionmaking in patients with VT. Detecting thrombus and localizing ischemic versus nonischemic scar had substantial impact on planned ablation approaches (endocardial vs epicardial and left vs right ventricular), in accordance with previously-published data. [8] In patients with pacemakers, scar assessment guided decisions regarding immunosuppression or device upgrade in sarcoidosis and genetic screening in patients with suspected cardiomyopathy. Across all CIEDs, new diagnoses (principally unexpected myocardial infarction or cardiomyopathies) were made in almost one in five patients.…”
Section: Safetymentioning
confidence: 99%
“…[1] This has led to an increase in demand for CMR [2] to determine the aetiology of heart failure, [3] assess viability, [4,5] prognosis, [6,7] and guide both coronary and electrophysiological interventions. [8] Alongside this rise in CMR, indications for cardiac implantable electronic devices (CIEDs) including permanent pacemakers (PPM) and implantable cardioverter defibrillators (ICD) are expanding, meaning that there are now 2.9 million people in the US alone with CIEDs. [9,10] Many of these patients with electrical abnormalities also have structural cardiac abnormalities, with LGE CMR clinically indicated to accurately assess scar to aid diagnosis and plan electrophysiological procedures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation